2021
DOI: 10.1111/mve.12524
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of zoonotic filarioids in Culex spp. from Portugal

Abstract: To investigate the role of dipterans in the transmission of Onchocerca lupi and other zoonotic filarioids, samples were collected from different sites in Algarve, southern Portugal, morphologically identified and molecularly tested for filarioids. Culex sp. (72.8%) represented the predominant genus followed by Culicoides sp. (11.8%), Ochlerotatus sp. (9.7%), Culiseta sp. (4.5%), Aedes sp. (0.9%) and Anopheles sp. (0.3%). Nineteen (2.8%) specimens scored positive for filarioids, with Culex pipiens quinquefascia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Despite not being featured in any peer-reviewed publication, there have been O. lupi sequences isolated from the heads and bodies of Simulium griseum from New Mexico, further supporting the putative role of black flies as suitable intermediate hosts. Several studies in Europe failed in the attempt to confirm the role of black flies and other biting flies as biological vectors of O. lupi, likely due to poor sampling (77, 85,86). It is known that this parasite species presents a wide geographic distribution; thus, the possibility of multiple arthropod species acting as vectors (e.g., as occurs with Onchocerca volvulus, the agent of river blindness in humans in Africa and Latin America) cannot be ruled out (87).…”
Section: Onchocerca Lupi Biologymentioning
confidence: 99%
“…Despite not being featured in any peer-reviewed publication, there have been O. lupi sequences isolated from the heads and bodies of Simulium griseum from New Mexico, further supporting the putative role of black flies as suitable intermediate hosts. Several studies in Europe failed in the attempt to confirm the role of black flies and other biting flies as biological vectors of O. lupi, likely due to poor sampling (77, 85,86). It is known that this parasite species presents a wide geographic distribution; thus, the possibility of multiple arthropod species acting as vectors (e.g., as occurs with Onchocerca volvulus, the agent of river blindness in humans in Africa and Latin America) cannot be ruled out (87).…”
Section: Onchocerca Lupi Biologymentioning
confidence: 99%
“…Before the advent of molecular techniques to identify filarial parasites, the detection of morphologically difficult to discriminate filarial larvae were typically only used to diagnose an arthropod vector as having zoonotic biting habits (Garms and Voelker 1969). The application of molecular techniques to screening of disease vectors has shown that precise identifications of filarial parasites can now be easily made from larvae found in vectors (Czajka et al 2014;Manoj et al 2021;Silva et al 2022). Many similar studies that have identified filarial parasites in arthropod vectors have, however, recovered DNA sequences from unknown adult parasite sources (Czajka et al 2012).…”
Section: Research Value Of Novel D Gracile Reference Sequencesmentioning
confidence: 99%
“…Recent surveys performed within the urban-forest interface zones of Manaus have found a diverse range of biting insects, but have not yet definitively incriminated any as a zoonotic disease bridge vector (Hendy et al 2020a;Hendy et al 2020b). Because filarial parasites usually cause chronic and persistent blood parasitaemias in their vertebrate hosts, they can often be detected in disease vectors, even when the vector is not a competent host for the parasite (Shelley et al 1994;Czajka et al 2012;Czajka et al 2014;Simonsen et al 2014;Manoj et al 2021;Silva et al 2022;). Because filarial parasites typically have limited host ranges, their detection in biting arthropods can and has been used to infer feeding preferences and, in this way, incriminate potential zoonotic disease bridge vectors (Garms and Voelker 1969;Lefoulon et al 2015;Crainey et al 2017a;Silva et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Cx. pipiens quinquefasciatus was identified as a competent vector in Algarve [147]. In Spain, the existence of Cx.…”
Section: Heartworm Vectorsmentioning
confidence: 99%